olve the radical equation.

3

2
(
x

6
)
5
=
6
3⋅
5

2(x−6)

=6

1 answer

To solve the equation

\[ 3 \cdot 2(x - 6)^5 = 6, \]

first, we can simplify the equation by dividing both sides by 3:

\[ 2(x - 6)^5 = 2. \]

Next, divide both sides by 2:

\[ (x - 6)^5 = 1. \]

Now, take the fifth root of both sides:

\[ x - 6 = 1. \]

Finally, add 6 to both sides to solve for \( x \):

\[ x = 1 + 6 = 7. \]

Thus, the solution to the equation is

\[ \boxed{7}. \]

Similar Questions
  1. solve the equation or formula for the indicated variable R=ts^2+3a)s=under radical R-3/t (not under radical b)s=everything under
    1. answers icon 2 answers
    1. answers icon 1 answer
  2. Find the area of the rectangle shown in the figure.length = radical (3) + radical (5) width = radical (3) + radical (5) My
    1. answers icon 0 answers
  3. Simplify by combining like terms.Problem #32 radical (63) - 2 radical (28) + 5 radical (7) My answer: 4radical(7) Problem #50
    1. answers icon 0 answers
more similar questions